Displacement due to violence in Columbia: Determinants and consequences at the household level - Stefanie Kirchhoff; Ana Maria Iba\~nez (University of Bonn, Center for Development Research (ZEF), 2001)
The armed conflict over economic and political power in Colombia has led to the massive displacement of people living in the areas of violence. The design of appropriate policies of prevention, assistance, and resettlement requires improved information on the determinants and effects of displacement. This paper contributes to providing such information by using household survey data collected at expulsory and receptor locations. First, we develop a conceptual framework for analyzing the factors which influence a household's decision to leave its area of origin for an uncertain future or to stay and risk being the victim of violence. Using econometric analysis, the framework is then used to examine the significance and relative importance of the hypothesized factors in the study region. Second, the impacts of displacement on the affected households are examined through a descriptive analysis of the survey data, and a method for estimating the welfare losses of the displaced is presented. The results confirm the significant role of violence and perceptions of insecurity in motivating displacement. The analysis indicates that land owners, members of local organizations, and younger household heads face the highest risk of becoming the direct target of threats which appear to be the most important trigger of displacement. However, security considerations do not appear to be the only factors underlying the displacement decision. People decide to stay in their areas of origin despite being affected by violence. A significant percentage of the displaced appear to have reflected on their options and on the expected impacts of displacement. Considerations regarding the cost of leaving behind important assets and potential improvements in living conditions after displacement appear to impact the decision. The results also point to the important role of information in displacement decisions. The descriptive analysis highlights the impacts of displacement on the affected households. The wide majority of the displaced had lived in the areas of origin for a very substantial amount of time. For many, displacement implies the loss of agricultural land and the associated way of life. At the receptor locations, households - particularly those from rural areas - have to look for types of employment they are not trained for. A very substantial proportion ends up being long-term unemployed. The surveys point to the need for programs which provide long-term opportunities to the displaced. The paper concludes with policy recommendations and topics for future research.
Keywords: 330; Consumer/Household Economics; Political Economy; Flüchtlinge; Bürgerkrieg; Umsiedlung; Wohlfahrtsanalyse; Schätzung; Kolumbien; Migrationstheorie